Unveiling 3D Morphology of Multiscale Micro‐Nanosilver Sintering for Advanced Electronics Manufacturing by Ptychographic X‐ray Nanotomography. Issue 4 (19th February 2020) - Lin, Yu-Chung; Liu, Xiaoyang; Chou, Kang Wei; Tsai, Esther H. R.; Zhao, Chonghang; Holler, Mirko; Diaz, Ana; Petrash, Stanislas; Chen-Wiegart, Yu-chen Karen
Abstract : The sintering processing–structure–property relationship of a multiscale silver materials is investigated: microparticles with nanofeatures, particularly on their three‐dimensional (3D) morphology. The target application is to replace conventional lead‐based solders in advanced electronic manufacturing. Unlike lead‐based solders, silver powders are suited to satisfy increasingly demanding mechanical, electrical, and thermal requirements, meanwhile being free of health effect. Sintering the material at a low temperature and without applied pressure are desirable conditions, which results in a preferred use of silver nanoparticles, as nanofeatures have higher driving force to sinter with the decrease in particle size. However, nanosized powders present potential health/environmental effects. To address the trade‐off between the benefits and shortcomings of nano‐ versus microparticles, this work studies a novel multiscale silver paste, namely micron‐sized powders with nanosized features. To get quantitative 3D visualization of micro‐ and nanoscale features, ptychographic X‐ray computed nanotomography is applied. The correlations between conditions (thermal aging, pressure, and substrate metallization), mechanical properties, and morphological parameters are established. Using novel 3D X‐ray nanoimaging technique, it is demonstrated that one can design multiscale materials while balancing complex demands required in advanced electronics manufacturing and research directions in materials design and characterization. Abstract : The sintering processing–structure–property relationship of a multiscale silver materials is investigated: microparticles with nanofeatures, particularly on their 3D morphology. Synchrotron ptychographic X‐ray computed nanotomography is applied to directly visualize the structure, as well as to establish correlations between processing conditions (thermal aging, pressure, and substrate metallization), mechanical properties (adhesive peel force), and 3D morphological parameters.